Analisis Keuangan Laporan Laba Rugi pada PT Kimia Farma Tbk Periode 2019-2023 - Novianti, Devy (Jurnal Riset Akuntansi, 2025)
Abstract. This study aims to analyze the financial performance of PT Kimia Farma Tbk based on the income statement for the period 2019–2023. The background of the research highlights the importance of financial statements as an evaluation tool to determine a company's profitability amidst business challenges. A descriptive quantitative approach is used, with secondary data sourced from the company's income statements. The data is analyzed using trend analysis methods to identify changes in revenue, expenses, and net income over five years. The results show that the company's revenue experienced a significant increase in 2020 and 2021 but declined sharply in 2022 before rising again in 2023. Net income showed similar fluctuations, with a significant decline in 2022 and a large loss in 2023. Operational and financial expenses increased drastically in 2023, indicating a lack of efficiency in cost management. The decline in non-operating income also played a significant role in affecting profitability. Despite revenue growth in some years, the company faces significant challenges in maintaining financial stability. Cost-efficiency strategies and improved management are needed to enhance profitability and the company's competitiveness. Abstrak. Penelitian ini bertujuan untuk menganalisis kinerja keuangan PT Kimia Farma Tbk berdasarkan laporan laba rugi periode 2019-2023. Latar belakang penelitian adalah pentingnya laporan keuangan sebagai alat evaluasi untuk menentukan profitabilitas perusahaan di tengah tantangan bisnis. Pendekatan yang digunakan adalah deskriptif kuantitatif dengan sumber data sekunder berupa laporan laba rugi perusahaan. Data dianalisis menggunakan metode analisis tren untuk mengidentifikasi perubahan pendapatan, beban, dan laba bersih selama lima tahun. Hasil penelitian menunjukkan bahwa pendapatan perusahaan mengalami peningkatan signifikan pada 2020 dan 2021, namun menurun tajam pada 2022 sebelum meningkat kembali pada 2023. Laba bersih menunjukkan fluktuasi serupa, dengan penurunan signifikan pada 2022 dan kerugian besar pada 2023. Beban operasional dan keuangan meningkat drastis pada 2023, menunjukkan kurangnya efisiensi dalam pengelolaan biaya. Penurunan pendapatan non-operasional juga menjadi faktor penting yang memengaruhi profitabilitas. Meskipun terdapat peningkatan pendapatan pada beberapa tahun, perusahaan menghadapi tantangan signifikan dalam menjaga stabilitas keuangan. Dibutuhkan strategi efisiensi biaya dan pengelolaan yang lebih baik untuk meningkatkan profitabilitas dan daya saing perusahaan.